Inhibition of glutathione peroxidase 4 suppresses gastric cancer peritoneal metastasis via regulation of RCC2 homeostasis - Can Hu; Jingli Xu; Yanqiang Zhang; Ruolan Zhang; Siwei Pan; Jiahui Chen; Yan Wang; Qianyu Zhao; Yuqi Wang; Weiwei Zhu; Mengxuan Cao; Shengjie Zhang; et al. (Redox Biology)
Gastric cancer (GC) is one of the most lethal malignancies due to high metastatic rate, making the identification of new therapeutic targets critical for developing effective anti-GC treatments. Glutathione peroxidase 4 (GPx4), a key regulator of ferroptosis and redox homeostasis, contributes to progression and influences patient survival. However, the molecular mechanism by which GPx4 drives GC progression has not been fully illuminated. In this study, we found that GPx4 was overexpressed and negatively associated with poor prognosis and distant metastasis, as confirmed by single-cell RNA sequencing (scRNA-seq) and validation with retrospective clinical samples. GPx4 knockdown suppressed GC invasion, migration and peritoneal metastasis in vitro and in vivo. Proteomic analysis revealed that GPx4 expression regulated the Homeostasis of RCC2, an oncogene link to epithelial-mesenchymal transition (EMT). Furthermore, we demonstrated that the reactive oxygen species (ROS) accumulation induced by GPx4 inhibition or knockdown activated aurora A phosphorylation, leading to RCC2 ubiquitination and degradation, thereby suppressing peritoneal metastasis in GC. We also identified that the Thr418 phosphorylation site is crucial for RCC2 ubiquitination at the K377, initiating its degradation in response to ROS. In conclusion, our results indicate that GPx4 acts as an oncogene in GC, and that suppressing GPx4 prevents GC progression and metastasis by promoting ROS-induced RCC2 ubiquitination and degradation.